Sinonasal Lymphoma Presenting as a Probable Sanctuary Site for Relapsed B Acute Lymphoblastic Leukaemia: A Case Report and Review of the Literature - Lim, W. Y.; Care, R.; Lau, M.; Chiruka, S.; Dawes, P. J. D. (Case Reports in Hematology, 2015)
Sinonasal lymphoma is a non-Hodgkin lymphoma (NHL) representing 1.5% of all lymphomas. It presents as an unremitting ulceration with progressive destruction of midline sinonasal and surrounding structures. Poor prognosis warrants early treatment although diagnosis is challenging and frequently delayed. It is usually primary in origin and to our knowledge the sinonasal region has never been reported as a sanctuary site in leukaemia/lymphoma relapse. We present a unique case of B-cell ALL (acute lymphoblastic leukaemia) with late relapse to the nasal septum as a sinonasal lymphoblastic lymphoma and with genetic support for this as a sanctuary site.